Proyecto de Factibilidad para la Implementacion de una Empresa Productora y Comercializadora de Cristales de Aloe Vera en la ciudad de Loja - Rosillo Vicente, Edi Rodolfo (2016)
Currently our country is experiencing low economic growth due to lack of business development, hence as student career Business Administration from the National University of Loja and a requirement for the degree of Engineer in Business Administration I have seen fit to make research called "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A PRODUCER AND MARKETER GLASS OF ALOE VERA IN THE CITY OF LOJA." The present work aims to create a product to be consistent with the needs, tastes, and preferences of the applicants in order to meet the expectations of them. Determine for this problem which is called "The lack of investment in production companies in the city of Loja income decreases and therefore the standard of living of its people", in the same way as was proposed objectives were raised the feasibility of implementing a producer and distributor of Aloe Vera Crystals business in the city of Loja; conducting a market study, Technical, 6 Organizational, Financial and Financial Evaluation with indicators to determine the different stages of the project. For the project took into account the following aspects: The corporate name of the company that is marketing specifically Crystals Aloe Vera "CRISÁBILA" CIA. Ltda. To be able to calculate the sample size is taken into account the population of the city of Loja 2015 is 194 070 inhabitants and 48 518 families, the sample size for this project is 397 surveys. When performing the market study showed the existence of unmet demand can be captured through an adequate effort to monopolize a certain percentage of the local market, because if there are marketing firms Crystals Aloe Vera in the city of Loja. This leads to through the Technical Study to determine the size, location, capacity, capacity utilization of the project and infrastructure required for operation, determining that the installed capacity of 262.800 thousand liters of annual Aloe Vera Crystals working with 3 workers, 3 industrial blenders and 3 filleting aloe, so that it can meet the needs of the applicants.